2017
DOI: 10.7205/milmed-d-16-00213
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Gender Differences in Thermoregulation

Abstract: In January 2013, the Department of Defense lifted a ban that had prevented women from holding combat positions in the military. However, innate differences in physical traits and physiology between men and women likely will result in differences in physical performance. Sex differences in thermoregulation is a key area that needs to be examined due to the potential impact on physical performance. Therefore, we expanded our previously developed thermoregulation model (TRM) to include the effects of gender. Wome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…in cross-sectional studies) can usually be attributed to higher body mass and metabolic heat production (higher absolute exercise intensities), rather than sex per se [104][105][106][107][108][109]. Taken together it seems that women are not at a thermoregulatory disadvantage compared with men for most activities and environmental conditions typically encountered [110,111]. As discussed in more detail elsewhere [109,110,112], other factors such as body size, surface area-to-mass ratio, heat acclimation status, aerobic capacity, exercise intensity, and environmental conditions (all of which directly or indirectly impact the evaporative requirement for heat balance) are more important than sex in determining sudomotor responses to exercise-heat stress.…”
Section: Chronicmentioning
confidence: 99%
“…in cross-sectional studies) can usually be attributed to higher body mass and metabolic heat production (higher absolute exercise intensities), rather than sex per se [104][105][106][107][108][109]. Taken together it seems that women are not at a thermoregulatory disadvantage compared with men for most activities and environmental conditions typically encountered [110,111]. As discussed in more detail elsewhere [109,110,112], other factors such as body size, surface area-to-mass ratio, heat acclimation status, aerobic capacity, exercise intensity, and environmental conditions (all of which directly or indirectly impact the evaporative requirement for heat balance) are more important than sex in determining sudomotor responses to exercise-heat stress.…”
Section: Chronicmentioning
confidence: 99%
“…It is very difficult because marked differences exist in the thermoregulatory mechanisms used by rodents vs. humans in overcoming hyperthermia (23). However, as women in the military and in athletics begin to approach levels of fitness of their male counterparts, concerns that women are inherently more susceptible than men to EHS (19,29,31) may be premature. For example, the most recent two years of military surveillance data in the US have demonstrated that although the proportion of men and women in active service who are diagnosed with exertional heat injury are approximately equal, the incidence of heat stroke in both 2015 and 2016 were 1.75-to 2.22-fold higher in men (3,4).…”
Section: Andmentioning
confidence: 99%
“…With the increasing participation and higher levels of performance of women in endurance athletics (30) and with higher expectations of women serving in active military service (41), there have been concerns regarding the susceptibility of women to exertional heat illness (EHI) and exertional heat stroke (EHS) (19,29,31). In military medicine, heat stroke is a subset of heat illness and in most cases it involves exertion in the heat.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be argued that the results seen in this meta-analysis can still be applied to females. This is because recent studies (Kaciuba-Uscilko and Grucza, 2001;Iyoho et al, 2017) have shown that there is no difference in heat adaptation and thermoregulation between male and females. Instead the rate of heat adaptation is linked to body surface area and surface mass ratio and, thus, the rate of heat adaptation is not dependant on gender (Notley et al, 2017).…”
Section: Limitationsmentioning
confidence: 96%